The use of intonation for turn anticipation in observed conversations without visual signals as source of information - Keitel, Anne; Daum, Moritz M. (Frontiers in Psychology, 2015)
The anticipation of a speaker’s next turn is a key element of successful conversation. This can be achieved using a multitude of cues. In natural conversation, the most important cue for adults to anticipate the end of a turn (and therefore the beginning of the next turn) is the semantic and syntactic content. In addition, prosodic cues, such as intonation, or visual signals that occur before a speaker starts speaking (e.g., opening the mouth) help to identify the beginning and the end of a speaker’s turn. Early in life, prosodic cues seem to be more important than in adulthood. For example, it was previously shown that 3-year-old children anticipated more turns in observed conversations when intonation was available compared with when not, and this beneficial effect was present neither in younger children nor in adults (Keitel, Prinz, Friederici, von Hofsten, & Daum, 2013). In the present study, we investigated this effect in greater detail. Videos of conversations between puppets with either normal or flattened intonation were presented to children (1-year-olds and 3-year-olds) and adults. The use of puppets allowed the control of visual signals: The verbal signals (speech) started exactly at the same time as the visual signals (mouth opening). With respect to the children, our findings replicate the results of the previous study: 3-year-olds anticipated more turns with normal intonation than with flattened intonation, whereas 1-year-olds did not show this effect. In contrast to our previous findings, the adults showed the same intonation effect as the 3-year-olds. This suggests that adults’ cue use varies depending on the characteristics of a conversation. Our results further support the notion that the cues used to anticipate conversational turns differ in development.